2014
DOI: 10.1248/bpb.b14-00359
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanism of Reproductive Dysfunction Caused by Neonicotinoid Pesticides

Abstract: Neonicotinoids, which were developed in the 1990 s as an insecticide having selective toxicity, were later found to cause reproductive abnormalities in experimental animals. In Japan there is an attempt to preserve endangered animals, including the Japanese crested ibis, and there is a question of whether neonicotinoids affect the reproduction of this bird, since they are used in its habitat. Hence, we investigated whether the daily oral administration of the neonicotinoid clothianidin (CTD) has any deleteriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…In red-legged partridges Alectoris rufa, reproductive effects included reduced clutch size, delayed laying dates and altered secondary sexual characteristics when exposed to imidacloprid (Lopez-Antia et al 2015a). Numbers of germ cells were reduced when Japanese quail Coturnix japonica were exposed to clothianidin (Hoshi et al 2014), while exposure of red-legged partridges to fipronil led to reductions in the levels of sex hormones, reduced egg fertility, and altered secondary sexual characteristics (Lopez-Antia et al 2015b). Imidacloprid and fipronil had deleterious effects on growth of birds, exhibited as growth retardation, reduced weight gain and lost body condition, often as a consequence of reduced food intake (Hussein et al 2014a, b;Khalil et al 2017;LopezAntia et al 2015b).…”
Section: Sublethal Effectsmentioning
confidence: 99%
“…In red-legged partridges Alectoris rufa, reproductive effects included reduced clutch size, delayed laying dates and altered secondary sexual characteristics when exposed to imidacloprid (Lopez-Antia et al 2015a). Numbers of germ cells were reduced when Japanese quail Coturnix japonica were exposed to clothianidin (Hoshi et al 2014), while exposure of red-legged partridges to fipronil led to reductions in the levels of sex hormones, reduced egg fertility, and altered secondary sexual characteristics (Lopez-Antia et al 2015b). Imidacloprid and fipronil had deleterious effects on growth of birds, exhibited as growth retardation, reduced weight gain and lost body condition, often as a consequence of reduced food intake (Hussein et al 2014a, b;Khalil et al 2017;LopezAntia et al 2015b).…”
Section: Sublethal Effectsmentioning
confidence: 99%
“…However, several studies have reported the disappearance and mass death of honeybees in Europe, as well as in America and other countries, occurring since the 1990s [18,21,65], which has raised concerns about the secondary effects of these agents on non-targeted insects. It has also recently been reported that NNs have adverse effects on vertebrates for example, on the reproductive organs in reptiles [9], birds [26,60] and mammals [67], and the emotional behavior in mice [23,24,59,68]. In order to assess the risk of NNs, therefore, there is an urgent need for definitive information about their effects on mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Neonicotinoids are taken up by plants and transported to all organs, including flowers, thus contaminating pollen and nectar as well as any fluid produced by the plant (3). There are increasing concerns about the impact of these systemic pesticides, not only on nontarget organismsespecially pollinators such as honey bees (4)(5)(6) and wild bees (7,8), as well as in other terrestrial and aquatic invertebrates (9, 10)-but also on vertebrates (11)(12)(13)(14), including humans (15,16). Impacts on such a broad range of organisms ultimately also affect ecosystem functioning (17).…”
mentioning
confidence: 99%